2023
DOI: 10.3389/fnut.2023.1094767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of molecular hydrogen supplementation on fatigue and aerobic capacity in healthy adults: A systematic review and meta-analysis

Abstract: BackgroundFatigue is oftentimes induced by high-intensity exercise potentially via the exceeded amount of reactive oxygen species, leading to diminished functions (e.g., aerobic capacity) and increased risk of injuries. Studies indicate that molecular hydrogen (H2), with antioxidant and anti-inflammatory properties, may be a promising strategy to alleviate fatigue and improve aerobic capacity. However, such effects have not been comprehensively characterized.ObjectiveTo systematically assess the effects of in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In a recent meta-analysis, Zhou et al, observed differences in the alleviation of exercise-induced fatigue by hydrogen across different training levels and types of exercise. Taken together, such benefits of H 2 may be associated with its antioxidative capacity ( 40 ), which, however, was not explicitly examined. Recent research efforts have been put to explore the effects of H 2 on oxidative stress in humans ( 23 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, Zhou et al, observed differences in the alleviation of exercise-induced fatigue by hydrogen across different training levels and types of exercise. Taken together, such benefits of H 2 may be associated with its antioxidative capacity ( 40 ), which, however, was not explicitly examined. Recent research efforts have been put to explore the effects of H 2 on oxidative stress in humans ( 23 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of molecular hydrogen on muscle tissue have not been extensively evaluated. Several studies indirectly asses this by evaluating the effects of molecular hydrogen on exercise performance, which clinical studies have demonstrated reduced lactate production [25] and levels of fatigue [26]. Animal studies demonstrate that H 2 treatment attenuated the exercise-induced increases in skeletal muscle TNF-α, NF-κB, IL-6, and caspase-3 levels while increasing superoxide dismutase levels [20].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that intaking hydrogen ( ), an antioxidant, holds great promise for helping to alleviate exercise-induced fatigue. 28 , 29 We previously observed that such effects of on fatigue are associated with its effects on the maintenance of PFC activation during the endurance exercise. Still, the effects of on the multiscale regulation of PFC hemodynamics, which can be assessed using fNIRS complexity, are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of different physical loads of endurance exercise on the fNIRS complexity of PFC, as well as the relationship between exercise-induced changes in fNIRS complexity and that of the underlying physiologic characteristics pertaining to fatigue (e.g., HR), have not been explicitly explored. Additionally, it has been shown that intaking hydrogen (normalH2), an antioxidant, holds great promise for helping to alleviate exercise-induced fatigue 28 , 29 . We previously observed that such effects of normalH2 on fatigue are associated with its effects on the maintenance of PFC activation during the endurance exercise.…”
Section: Introductionmentioning
confidence: 99%